2017
DOI: 10.1016/j.appdev.2017.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal associations between teacher-child interactions and academic skills in elementary school

Abstract: This study examined the extent to which the quality of teacher-child interactions assessed in kindergarten (6-year-olds) is associated with children's reading and math development across the elementary school years. The sample consisted of 515 Finnish children (271 boys, 244 girls). Teacher-child interactions were observed in 49 kindergarten classrooms. The findings from the latent growth curve models showed that high-quality teacher-child interactions in kindergarten were positively associated with the initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…To the best of our knowledge, no previous study has examined whether students' cognitive engagement affects the quality of the teacher-student relationship in general, or more specifically, teacher-student conflict. Yet, consistent with the idea that students evoke teacher behavior in line with the students' engagement levels, students who are more cognitively engaged in school and value education may be less involved in conflicted relationships with their teachers (Nurmi & Kiuru, 2015;Skinner & Belmont, 1993). The current study investigates this possibility for cognitive engagement.…”
Section: Cognitive Engagementmentioning
confidence: 82%
“…To the best of our knowledge, no previous study has examined whether students' cognitive engagement affects the quality of the teacher-student relationship in general, or more specifically, teacher-student conflict. Yet, consistent with the idea that students evoke teacher behavior in line with the students' engagement levels, students who are more cognitively engaged in school and value education may be less involved in conflicted relationships with their teachers (Nurmi & Kiuru, 2015;Skinner & Belmont, 1993). The current study investigates this possibility for cognitive engagement.…”
Section: Cognitive Engagementmentioning
confidence: 82%
“…Furthermore, given longitudinal associations in the literature between early teacher–student relationships and interactions and students’ academic achievement (e.g., Pakarinen et al, 2017; Spilt, Hughes, et al, 2012), potential effects of BEST in CLASS-E from the current study on teacher-reported closeness may also potentially contribute to distal student outcomes. The effect size in the current study was 0.55, compared with a smaller effect ( d = 0.26) noted in the BEST in CLASS preschool study (Sutherland, Conroy, Algina, et al, 2018).…”
Section: Discussionmentioning
confidence: 93%
“…There is some evidence that behaviour problems may lead to poor TSR quality (e.g. Hopman et al, 2019;Pakarinen et al, 2017), while others have found that a difficult TSR is associated with subsequent behaviour problems or that a reciprocal association exists (Doumen et al, 2008;Zhang & Sun, 2011). Secondly, only teacher-reports were used and were collected at a single time point; therefore, shared reporter variance may have resulted in the significant associations.…”
Section: Limitationsmentioning
confidence: 99%